Posouzení finančního zdraví firmy - Karas, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Bakalářská práce hodnotí finanční zdraví společnosti Anamoka, s.r.o. . Při finanční analýze firmy jsem využil elementárních metod finanční analýzy. Analyzoval jsem účetní závěrku (rozvaha, výkaz zisku a ztrát) firmy z let 2004 – 2006. Na základě výsledků finanční analýzy jsem navrhl doporučení ke zlepšení finanční situace firmy.

This bachelor thesis analyzes the financial position of the company Anamoka, s.r.o. I have analysed the financial position of this copany by using elementary methods of Financial analysis. I have analyse company´s financial statements (balance sheet, profit and loss account) from years 2004, 2005, 2006. On the basis of findings from financial analysis, I have created proposals for improvement of company´s financial position.
Analysis of Company´s Financial
Keywords: finanční analýza; Altmanův index; IN01; quicktest; pohledávky; faktoring; financial analysis; Altman´s index; IN01; quicktest; active debts; factoring